Comparison of Light Emitting Diode (LED) Fluorescent Microscopy with Ziehl-Neelsen Microscopy on Sputum Specimens for Diagnosis of Pulmonary Tuberculosis Keeping Culture as ‘Gold Standard’ - Zahra, Fatima Tuz; Saleem, Muhammad Zeeshan; Mirza, Irfan Ali; Sana, Fatima; Hussain, Ashfaq; Zaman, Syed Qamar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare LED fluorescence microscopy and Ziehl-Neelsen staining in terms of their diagnostic performance in diagnosing pulmonary tuberculosis, taking sputum specimens from patients suspected of pulmonary tuberculosis. Study Design: Prospective longitudinal study. Place and Duration of Study: Microbiology Department, Armed Forces Institute of Pathology Rawalpindi, from Jan 2019 to Dec 2019. Methodology: Sputum samples from patients with clinical suspicion of pulmonary tuberculosis were stained using Ziehl-Neelsen (ZN) stain, fluorescent stain with Auramine O staining (AO) stain and Mycobacterial culture on Mycobacterial Growth Indicator Tube (MGIT 960), to detect Mycobacterium tuberculosis. WHO guidelines were followed to grade positive smears. Results: Among 206 patients with suspicion of tuberculosis, 143 (69%) were male, and 63 (30%) were female patients. The mean age of the patients was 53.67 ± 14.73 years. Out of 206 sputum samples, 64 were negative by all three techniques used. 142 (68%) specimens detected Mycobacterium tuber-culosison MGIT960. Within 142 culture-positive samples, only 40 samples were positive on Ziehl-Neelsen microscopy, whereas 97 samples were detected positive by LED fluorescent microscopy. In culture-negative samples, three were missed on Ziehl-Neelsen staining, which was positive with Fluorescent microscopy. Sensitivity and specificity for Ziehl-Neelsen smear microscopy were 26.7% and 96.8%, respectively. Sensitivity and specificity for Fluorescent smear microscopy were 64.8% and 92.2%, respectively. Conclusion: We concluded that the efficacy of LED fluorescence microscopy has proven to have many potential advantages over conventional Ziehl-Neelsen microscopy.